(untitled) (Bangladesh Heart Journal, 2021)
Background: Vascular access care is a classic example of multidisciplinary team work among nephrologists, vascular surgeons, duplex specialists, dialysis nurses and dialysis staff. The objectives of this study were to determine the complication of arteriovenous fistula (AVF) for hemodialysis (HD) and to find out the role of duplex study for the management of fistula complications. Methods: This was a prospective type of study done on 121 arteriovenous fistulas. All operations were done in different hospitals in Dhaka city. After duplex study of upper limb vessels, the site of fistula creation was determined. All Radio-cephalic, ulnar-basilic and brachiocephalic fistulas were done under local anesthesia. Other fistula of the series was done under brachial block. Immediate postoperative bruit, thrill and distal pulses were monitored. Fistulas were considered mature after at least 6 weeks of fistula creation with good visualization of arterialized vein and good thrill. Patients were advised to report if any complication arises. Results: The most common fistula was Radio-cephalic fistulas (72.73%) and then Brachio-cephalic fistulas (19.84%). The left upper limb was the first choice for fistula creation as a non-dominant limb. Most fistula was created in left upper limb (76.86%). The most common complication was stenosis of arterialized veins (4.13%) and another type of stenosis was found at anastomotic site (2.48%). Second most common complication was cannulation site infections (3.31%). Another common type of infection was found at the site of fistula creation (2.48%). Thrombosis, aneurysm and pseudoaneurysm were identified as the most detrimental complications. Conclusion: Arteriovenous fistula is an important issue for hemodialysis patient as the life line. Dialysis nurses and technician should have knowledge about antisepsis and potential complication of AVFs. Early diagnosis and early treatment prevent loss of vascular access and reduce serious morbidity and mortality. Both the patients and dialysis staffs should give highest care for the AVF to reduce the complications. Bangladesh Heart Journal 2020; 35(2) : 100-105